Perilesional edema in radiation necrosis reflects axonal degeneration - Perez-Torres, Carlos J (Radiat Oncol, 2015)
BACKGROUND: Recently, we characterized a Gamma Knife® radiation necrosis mouse model with various magnetic resonance imaging (MRI) protocols to identify biomarkers useful in differentiation from tumors. Though the irradiation was focal to one hemisphere, a contralateral injury was observed that appeared to be localized in the white matter only. Interestingly, this injury was identifiable in T2-weighted images, apparent diffusion coefficient (ADC), and magnetization transfer ratio (MTR) maps, but not on post-contrast T1-weighted images. This observation of edema independent of vascular changes is akin to the perilesional edema seen in clinical radiation necrosis. FINDINGS: The pathology underlying the observed white-matter MRI changes was explored by performing immunohistochemistry for healthy axons and myelin. The presence of both healthy axons and myelin was reduced in the contralateral white-matter lesion. CONCLUSIONS: Based on our immunohistochemical findings, the contralateral white-matter injury is most likely due to axonal degeneration.